2011
DOI: 10.3389/fnsys.2011.00017
|View full text |Cite
|
Sign up to set email alerts
|

Reduced GABA Content in the Motor Thalamus during Effective Deep Brain Stimulation of the Subthalamic Nucleus

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN), in Parkinson's disease (PD) patients, is a well established therapeutic option, but its mechanisms of action are only partially known. In our previous study, the clinical transitions from OFF- to ON-state were not correlated with significant changes of GABA content inside GPi or substantia nigra reticulata. Here, biochemical effects of STN-DBS have been assessed in putamen (PUT), internal pallidus (GPi), and inside the antero-ventral thalamus (VA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 46 publications
4
31
0
2
Order By: Relevance
“…The mechanisms by which STN-DBS affects thalamic activity have not been adequately worked out, although as mentioned earlier, the upstream GPi is likely an important player. Supporting this idea, microdialysis sampling of GABA content in the VA thalamus has revealed reductions in this transmitter during DBS (Stefani et al, 2011), possibly due to inhibition of pallidal afferents.…”
Section: Circuit Modulations During Deep Brain Stimulation At the Stnmentioning
confidence: 89%
“…The mechanisms by which STN-DBS affects thalamic activity have not been adequately worked out, although as mentioned earlier, the upstream GPi is likely an important player. Supporting this idea, microdialysis sampling of GABA content in the VA thalamus has revealed reductions in this transmitter during DBS (Stefani et al, 2011), possibly due to inhibition of pallidal afferents.…”
Section: Circuit Modulations During Deep Brain Stimulation At the Stnmentioning
confidence: 89%
“…These differential effects of STN/GPi DBS on thalamic activity are further supported by micro-dialysis studies examining the change in neurotransmitter levels in the thalamus during DBS. Stefani et al have reported reduced levels of GABA in the VA, during STN DBS [28], suggesting a reduction in GPi output to the VA and could potentially correlate with the subset of units that were excited during DBS in this study. This finding would suggest that DBS suppresses output from the stimulated structure.…”
Section: Discussionmentioning
confidence: 60%
“…This finding would suggest that DBS suppresses output from the stimulated structure. Multiple other studies, however, have reported increased cGMP levels in the GPi [28] [29] [30] and in the SNr [30] during STN DBS suggesting increased levels of synaptic/metabolic activity consistent with activation of output from the stimulated structure. Regardless of whether one supports the inhibition or activation hypothesis, the far-reaching effect of DBS on other structures in the circuit is supported by a number of studies demonstrating alterations in cortical activity with STN [31] [32] or GPi DBS [33] as well as previous modeling [34,35] and animal studies recording from multiple structures in the circuit [9,24] [3638].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated increased glutamate levels in the GPi and putamen as well as reduced GABA levels in the motor thalamus during active HFS [5]. Their data confirm that STN HFS results in increased glutamatergic projections from STN to GPi and, subsequently, GABAergic projections from the GPi to the motor thalamus, thus normalising thalamic inhibition and reducing symptoms of the hyperkinetic state.…”
Section: Discussionmentioning
confidence: 68%
“…Invasive techniques such as in-vivo microdialysis provide the possibility to directly assess neurotransmitter levels in subcortical brain areas in humans [4,5]. Further, the combination of microdialysis and functional neurosurgical methods enables the study of neurochemical effects of high-frequency stimulation (HFS) in otherwise inaccessible human subcortical structures.…”
Section: Introductionmentioning
confidence: 99%